Ineffective health control: concept analysis - Wenysson Noleto dos Santos; Rudval Souza da Silva; Francisca Marta de Lima Costa Souza; Rebecca Stefany da Costa Santos; Izaque Cavalcanti de Oliveira; Richardson Augusto Rosendo da Silva
ABSTRACT Objectives: to identify and synthesize the concept of Ineffective Health Control. Methods: Concept Analysis from the perspective of Walker and Avant, operationalized by an integrative review in the databases Scopus, LILACS, PubMed, CINAHL, Web of Science, Science Direct e Cochrane, using the descriptors: Adhesion to Medication; Cooperation and Adherence to Treatment and Acquired Immunodeficiency Syndrome. Results: five critical attributes were identified for the concept, namely: patient's refusal to follow the therapeutic plan; abandoning treatment and worsening signs and symptoms; difficulty in reaching agreed goals; difficulty following health professionals' guidelines; multifactorial and dynamic process. Conclusions: the concept of Ineffective Health Control is characterized by a multifactorial and dynamic process evidenced by the patient's refusal to follow a therapeutic plan, favouring the abandonment of treatment and resulting in the worsening of signs and symptoms and failure to reach goals.